Professor Leonas Jovaiša as the Foundation Builder of the System of Education Science - Aramavičiūtė, Vanda (Acta Paedagogica Vilnensia, 2005)
The articles addresses the topicality of the holistic system of education in the contemporary world. Also, it is maintained and evidence is provided to support the attitude that the application of the systemic principle is essential for the shaping of the holistic approach to education. The systemic principle enables one to discover and explore separate systems of education, furthermore, it enhances the processed of creating new educational systems as well as controlling their management processed. Within the framework of this context, the invaluable contribution of Professor L Jovaiša is revealed on the way to establishing and cherishing the systemic approach to the Lithuanian educational science. The article discusses, in a systemic way, the general foundation issues of the educational science as defined by Professor L. Jovaiša: philosophical, psychological and socio-cultural. The system of moral education of personality is also addressed in the article – as a significant domain of educational science. The issues of specific systems of methods alongside the major principles, aims and objectives of education are also focused on in the article.
Keywords: educational system; systemology; educational structure